Factors Associated with Lymph Node Count in Mucosal Squamous Cell Carcinoma Neck Dissection. (4th January 2021) - Bhalli, Hamza; Chen, Shuqing; Day, Andrew; Tillman, Brittny; Gordin, Eli; Truelson, John; Sher, David; Myers, Larry; Gao, Jinming; Sumer, Baran D.
Abstract : Objective/Hypothesis: Decreased lymph node count (LNC) from neck dissection (ND) for mucosal head and neck squamous cell carcinoma (HNSCC) patients is correlated with decreased survival. Advanced age and low BMI due to undernutrition from dysphagia from advanced T‐stage tumors are common in patients with HNSCC. We studied the relationship between these two well‐described causes for immune dysfunction and LNC in patients undergoing neck dissection. Study Design: We conducted a retrospective review at a single tertiary care institution of patients with HNSCC that underwent neck dissection from 2006 to 2017. Methods: Stepwise linear and logistic regression analyses were performed on 247 subjects to identify independent significant factors associated with 1) the LNC per neck level dissected; 2) advanced T‐stage. One‐way ANOVA was utilized to demonstrate differences between the p16 positive and negative subgroups. Results: Low BMI (<23 vs. ≥23) ( P = .03), extra nodal extension (ENE) ( P = .0178), and advanced age ( P = .005) were associated with decreased LNC per neck level dissected on multivariable analysis. Higher T‐stage ( P = .0005) was correlated with low BMI (<23) after controlling for the effects of tobacco, smoking, sex, ECE, and p16 status. p16+ patients, on average had higher BMI, were younger and produced a higher nodal yield ( P < .0001, .007, and .035). Conclusions: Patient intrinsic factors known to correlate with decreased immune function and worse outcomes, including p16 negative status, advanced age, and low BMI from undernutrition and ENE are associated with low nodal yield in neck dissections. LNC may be a metric for anti‐tumor immune function that correlates with prognosis and T‐stage. Level of Evidence: 3 Laryngoscope, 131:1516–1521, 2021